The concept of mind in Hindu Tantrism - Flood, G (Oxford University Press, 2021)
This article presents an account of the mind as found in pre-philosophical and philosophical Śaiva and Śaiva-Śākta literature and examines some important terms that the English word translates, notably, citta, cit, and manas, although there are others, mostly in the medieval or post-Gupta period. Through such inquiry, we see an ambivalent attitude towards the category mind, on the one hand, being a cause of bondage, while, on the other, being elevated to the highest ontological category. Such an examination raises interesting historical questions about influences on the Śaiva and Śaiva-Śākta material and interesting philosophical questions about the category mind in relation to the category of the person.